PDK2 leads to cisplatin resistance through suppression of mitochondrial function in ovarian clear cell carcinoma. Issue 11 (13th September 2021) - Kitamura, Sachiko; Yamaguchi, Ken; Murakami, Ryusuke; Furutake, Yoko; Higasa, Koichiro; Abiko, Kaoru; Hamanishi, Junzo; Baba, Tsukasa; Matsumura, Noriomi; Mandai, Masaki
Abstract: Ovarian clear cell carcinoma (CCC) exhibits an association with endometriosis, resistance to oxidative stress, and poor prognosis owing to its resistance to conventional platinum‐based chemotherapy. A greater understanding of the molecular characteristics and pathogenesis of ovarian cancer subtypes may facilitate the development of targeted therapeutic strategies, although the mechanism of drug resistance in ovarian CCC has yet to be determined. In this study, we assessed exome sequencing data to identify new therapeutic targets of mitochondrial function in ovarian CCC because of the central role of mitochondria in redox homeostasis. Copy number analyses revealed that chromosome 17q21‐24 (chr.17q21‐24) amplification was associated with recurrence in ovarian CCC. Cell viability assays identified an association between cisplatin resistance and chr.17q21‐24 amplification, and mitochondrion‐related genes were enriched in patients with chr.17q21‐24 amplification. Patients with high expression of pyruvate dehydrogenase kinase 2 (PDK2) had a worse prognosis than those with low PDK2 expression. Furthermore, inhibition of PDK2 synergistically enhanced cisplatin sensitivity by activating the electron transport chain and by increasing the production of mitochondrial reactive oxygen species. Mouse xenograft models showed that inhibition of PDK2 with cisplatin inhibited tumor growth. This evidence suggests that targeting mitochondrial metabolism and redox homeostasis is an attractive therapeutic strategy for improving drug sensitivity in ovarian CCC. Abstract : Copy number analyses and cell viability assays identified an association between cisplatin resistance and chromosome 17q21‐24 (chr.17q21‐24) amplification, and mitochondrion‐related genes were enriched in patients with chr.17q21‐24 amplification. Patients with high expression of pyruvate dehydrogenase kinase 2 (PDK2), a key enzyme that inhibits acetyl‐CoA from entering the tricarboxylic acid cycle and is located on chr.17q23, had a worse prognosis than did those with low PDK2 expression. Inhibition of PDK2 synergistically enhanced cisplatin sensitivity by activating the electron transport chain and by increasing the production of mitochondrial reactive oxygen species.